Isosorbide mononitrate promotes angiogenesis in embryonic development of zebrafish - Hui Lv; Bo Liu; Yongwen Qin (Genetics and Molecular Biology, 2020)
Abstract Coronary heart disease (CHD) is a leading cause of death worldwide, and angiogenesis plays important roles in CHD. Thus, in the present study, the angiogenic efficacy of four common cardiovascular medicines (aspirin, pravastatin, metoprolol and isosorbide mononitrate (ISMN)) was determined by the number and length of zebrafish intersegmental vessels (ISVs) after immersing zebrafish embryos in different medicines. Results showed that ISMN significantly increased the length and number of ISVs. ISMN is a long-acting nitrate ester drug. It has been used as a vasodilator to dilate arteries and veins to reduce the cardiac preload and postload. However, the effect of ISMN on angiogenesis remains unclear. Thus, by in vitro experiments, the angiogenic mechanism of ISMN was evaluated through detecting the viability and proliferation of human umbilical vein endothelial cells (HUVECs) and the expression of angiogenesis-related genes and miRNAs. Results indicated that ISMN could increase the viability and proliferation of HUVECs by decreasing apoptosis, and elevated the expressions of vedf, kdrl, pdgfr in zebrafish embryos. Furthermore, the expressions of miR-126, miR-130a and miR-210 were also regulated in ISMN-treated HUVECs. In conclusion, ISMN could promote angiogenesis in zebrafish embryos and HUVECs, implying ISMN may be a potential therapeutic in treating angiogenesis-related diseases.